-4(3y-8)+3(2y+8)=

Simple and best practice solution for -4(3y-8)+3(2y+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3y-8)+3(2y+8)= equation:


Simplifying
-4(3y + -8) + 3(2y + 8) = 0

Reorder the terms:
-4(-8 + 3y) + 3(2y + 8) = 0
(-8 * -4 + 3y * -4) + 3(2y + 8) = 0
(32 + -12y) + 3(2y + 8) = 0

Reorder the terms:
32 + -12y + 3(8 + 2y) = 0
32 + -12y + (8 * 3 + 2y * 3) = 0
32 + -12y + (24 + 6y) = 0

Reorder the terms:
32 + 24 + -12y + 6y = 0

Combine like terms: 32 + 24 = 56
56 + -12y + 6y = 0

Combine like terms: -12y + 6y = -6y
56 + -6y = 0

Solving
56 + -6y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + -6y = 0 + -56

Combine like terms: 56 + -56 = 0
0 + -6y = 0 + -56
-6y = 0 + -56

Combine like terms: 0 + -56 = -56
-6y = -56

Divide each side by '-6'.
y = 9.333333333

Simplifying
y = 9.333333333

See similar equations:

| An=n+7 | | 10-4x+5x=7 | | 4(3x-6)-2=4(x-4)+30 | | N=200+30t-t^2 | | 9x-4=22x-2 | | 8-2(11-5)/3= | | 2x-7+7x-2= | | x^2-13=18 | | 5y+7=13y+7 | | 144-6(-12)= | | 0.75x+x= | | 11+b=2-2b | | -3(5p+6)-2(6-17p)=3(9+6p) | | 10-9x-7-5x=5 | | x-2x=108 | | 3(x+5)-6= | | 7x+2z=8+8y | | ln(x+14)-ln(8-3x)=3ln(2) | | 8=-116+n | | lnx+ln(x-2)=2ln(x-3) | | (7/10)-(8/15) | | 4(7i-5)=6(4i-2) | | 11/16-1/48 | | 1/48-11/16 | | -10x+5=7x+5 | | 4x+7=6-24x+36 | | 43/30 | | f(t)=0.2t^2+0.03t^3 | | 57=(x+2)x | | (5-u)(5u-6)=0 | | 3x-3+2x=52 | | -4(y+1)(-y+6)=0 |

Equations solver categories